Pertimbangan Hakim Dalam Perceraian Agama Kristen Di Pengadilan Negeri Padang Kelas 1a (Studi Kasus No 110/Pdt.G/2024/Pn Pdg) - Yulius Rico Andrianto; Engrina Fauzi (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
Divorce in Christian teachings is fundamentally discouraged as it is considered contrary to Biblical principles, particularly in Matthew 19:5–6, which states that marriage is a sacred union that must not be separated by humans. This study aims to analyze the considerations of judges at the Padang District Court in granting a divorce lawsuit involving a Christian couple in Case Number 110/Pdt.G/2024/PN Pdg, as well as to examine its conformity with Protestant church doctrine. The research method used is normative juridical with a statutory and case study approach. The results indicate that the judges granted the divorce based on Law Number 16 of 2019, considering factors such as ongoing disputes, neglect of the husband’s obligations, physical violence, and prolonged separation as regulated in Article 39 of the Marriage Law in conjunction with Article 19 of Government Regulation Number 9 of 1975. However, the decision is not in line with Protestant church teachings, which only recognize divorce in the event of death. This creates a dualism of law, where the couple is legally divorced under state law but remains bound according to church doctrine. The study concludes that there is a fundamental difference between state law and church doctrine in viewing divorce. Therefore, it is necessary to enhance understanding of the sanctity of marriage in Christian teachings, strengthen the role of church counseling and mediation, and encourage cooperation between the courts and the church in handling divorce cases to minimize the negative impacts arising from this discrepancy.